2012 38th IEEE Photovoltaic Specialists Conference 2012
DOI: 10.1109/pvsc.2012.6318300
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atmospheric variations on photovoltaic performance and modeling their effects for days with clear skies

Abstract: Although variation in photovoltaic (PV) performance is predominantly influenced by clouds, performance variations also exist for days with clear skies with different amounts of atmospheric constituents that absorb and reflect different amounts of radiation as it passes through the Earth's atmosphere. The extent of the attenuation is determined by the mass of air and the amounts of water vapor, aerosols, and ozone that constitute the atmosphere for a particular day and location.Because these constituents select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 4 publications
(3 reference statements)
1
8
0
Order By: Relevance
“…Work is being performed to address thin-film PV metastabilities (Deline et al, 2012;Silverman et al, 2014) to provide more accurate measurements of P 0 in the future. Departures of stacked-bar values from one for the a-Si and CdTe PV modules are consistent with previous work in which the sensitivity of PV performance to variations in atmosphere for days with clear skies was studied (Marion, 2012). The extent of attenuation of solar radiation by the atmosphere is determined primarily by the mass of air and the amounts of water vapor, aerosols, and ozone.…”
Section: Resultssupporting
confidence: 87%
“…Work is being performed to address thin-film PV metastabilities (Deline et al, 2012;Silverman et al, 2014) to provide more accurate measurements of P 0 in the future. Departures of stacked-bar values from one for the a-Si and CdTe PV modules are consistent with previous work in which the sensitivity of PV performance to variations in atmosphere for days with clear skies was studied (Marion, 2012). The extent of attenuation of solar radiation by the atmosphere is determined primarily by the mass of air and the amounts of water vapor, aerosols, and ozone.…”
Section: Resultssupporting
confidence: 87%
“…This analysis is based on the estimation of the spectral impact of degradation mechanisms by taking into account multiple spectra with different values of air mass (AM), aerosol optical depth (AOD) and precipitable water (PW). It has been demonstrated that these three atmospheric parameters are the most influential on the spectral irradiance in clear-sky days, and they are widely used to analyse the effect of solar spectrum variations on the performance of PV devices [141][142][143][144]. Table 2 includes the wavelength limits of the absorption band of each material along with the limits of the different spectral regions that have been considered in this study.…”
Section: Agingmentioning
confidence: 99%
“…However, STC conditions are a rather infrequent yearly occurrence for most of the world; therefore, an alternative temperature may be chosen more representative of the average annual temperature [40]. Additional considerations not discussed here may include corrections for angle of incidence [45] or for spectral effects [46].…”
Section: Decision Treesmentioning
confidence: 99%